Characteristics of human encephalitis caused by pseudorabies virus: A case series study. (October 2019) - Yang, Xue; Guan, Hongzhi; Li, Chen; Li, Ying; Wang, Shengjun; Zhao, Xiuhe; Zhao, Yuying; Liu, Yiming
Highlights: Pseudorabies virus (PRV) can cause illnesses in humans. A case series of five patients with PRV encephalitis is reported. PRV should be considered in patients with a central nervous system infection. Abstract: Background: Pseudorabies virus (PRV) has been thought to cause diseases only in animals. However, recent studies have shown that PRV can also cause illnesses in humans. Methods: This was a case series study. The cases of five patients with clinical symptoms of acute encephalitis, which were confirmed to be caused by PRV infections, were reviewed. Case presentation: The five patients all had jobs involving the handling of pigs. They had acute onset and rapid progression of clinical presentations, which were consistent with central nervous system infections. Four of them had respiratory failure, which required ventilator support. Brain magnetic resonance imaging showed abnormal signals in the bilateral temporal lobes and insular cortex in all five patients, bilateral frontal lobes in one patient, and caudate nucleus in one patient. Cerebrospinal fluid analysis results were consistent with a viral infection. Next-generation sequencing of the cerebrospinal fluid confirmed the presence of PRV. All patients received human immunoglobulin, glucocorticoids, antiviral agents, and symptomatic supportive treatments. All patients survived until discharge, but suffered from various sequelae. Pneumonia was the most common complication during the disease course. Conclusions: PRV encephalitis should be included in the differential diagnosis of patients with a clinical presentation of central nervous system infection, especially for those who have had recent contact with pigs.